New insights into Li diffusion in Li–Si alloys for Si anode materials: role of Si microstructures. Issue 29 (16th July 2019) - Wang, Guoqing; Xu, Bo; Shi, Jing; Wu, Musheng; Su, Haibin; Ouyang, Chuying
Abstract : The effect of Si microstructures on Li diffusion in Li–Si alloys was studied by using first-principles molecular dynamics calculations. The relationship between aggregation degree of Si and Li diffusion coefficients is established. Abstract : Li ion transport is very important to the rate capability of electrode materials in Li ion batteries. For Si anodes, due to huge structural changes of Si structures during the process of charging and discharging, Li ion transport is essentially affected by the Si internal microstructures. Herein, we studied the effect of Si microstructures on Li ion diffusion in Li–Si alloys using first-principles molecular dynamics calculations. Our results demonstrate that the Li diffusion coefficients are closely related to the aggregation degree of Si atoms, regardless of whether it is the low Li concentration phase LiSi or the high Li concentration phase Li2 Si under consideration. Furthermore, through counting the number of Si microstructures, such as rings, chains and small clusters, the relationship between the aggregation degree of Si atoms and the number of Si microstructures is established. A large number of Si microstructures corresponds to the low aggregation degree of Si atoms, thus resulting in small Li diffusion coefficients due to the strong interaction between Li and Si atoms. Conversely, a small number of Si microstructures originates from the high aggregation degree of Si atoms, consequently leading to large Li diffusion coefficients. Our study provides a deep insight into the relationship between the Li ion diffusion and the Si distribution, which facilitates the performance improvement of future Si anode materials.